Performance of Cu‐Fe‐based oxygen carrier in a CLC process based on fixed bed reactors. Issue 4 (24th April 2017) - Tian, Qiang; Che, Lixin; Ding, Bin; Wang, Qianwei; Su, Qingquan
Abstract: To explore the application of chemical‐looping combustion (CLC) to the distributed medium‐ small‐scale hot water and steam gas‐fueled boilers, a CLC process based on two fixed bed reactors (FBRs) has been proposed. A Cu‐Fe‐based oxygen carrier (OC) was studied to meet the requirements for this process. Results showed that Cu30‐Fe50/Al20 was exothermic both in the reduction step and in the oxidation step, and showed a quite large operating temperature window of 600–900°C. At the lower temperature side, it showed good low temperature reactivity, and at the higher temperature side, it showed strong resistance to carbon deposition, agglomeration, and sintering. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd.